Abbasova, Ayten - (:unkn) unknown (My University, 2026)
Ayten Abasova Asgar entered the Faculty of Civil Engineering at the Azerbaijan Institute of Civil Engineers in 1985 and graduated in 1990 with a degree in Industrial and Civil Construction. She began her professional career in 1990 as a Design Engineer at the Southern Agro-Industrial Design Institute. In 1997, she joined the Azerbaijan University of Architecture and Construction as a Senior Laboratory Assistant at the Department of Strength of Materials. She was appointed Senior Lecturer in 1999, awarded the academic title of Associate Professor in 2004, and since 2007 has been a faculty member of the Department of Business Economics and Management. Her academic and professional activities focus on teaching and research in the fields of business economics, management, and engineering education.